Global Entrepreneurship Monitor Caribbean : Social Entrepreneurship, In The Caribbean Región : 2011 (2012)
The main indicator the Global Entrepreneurship Monitor (GEM) measures is Total Entrepreneurial Activity (TEA), that is, the percentage of the adult population aged 18-64 actively involved in the establishment and/or managing of a business which has been paying salaries for less than 42 months. The study determined that there are big differences between the TEAs from city to city and region to region in Colombia. Some policy recommendations are formulated and new research lines identified to advance support mechanisms toward entrepreneurship development. en